"O parňipen but kerel adádžive / That you're white, it does a lot today" With Marcel Klempar about working abroad and what it has brought him - Kubaník, Pavel; Ort, Jan; Peterková, Kornélie (Romano džaniben, 2023)
Marcel Klempár from Medzev, eastern Slovakia, describes his stays abroad - in the Czech Republic, Germany, and especially in Holland, where he lived for a long time with his family. He frames this experience as a story of social mobility, but also as a means to critically examine the marginalization of Roma in the environment of a town in eastern Slovakia.
Keywords: work abroad; migration; social mobility; racism; eastern Slovakia